Mesopelagic respiration near the ESTOC (European Station for Time-Series in the Ocean, 15.5°W, 29.1°N) site inferred from a tracer conservation model - Fernández-Castro, B.; Arístegui, J.; Anderson, L.; Montero, M. F.; Hernández-León, S.; Marañón, E.; Mouriño-Carballido, B. (Deep Sea Research Part I: Oceanographic Research Papers, 2016)
Remineralization of organic matter in the mesopelagic zone (ca. 150–700 m) is a key controlling factor of carbon export to the deep ocean. By using a tracer conservation model applied to climatological data of oxygen, dissolved inorganic carbon (DIC) and nitrate, we computed mesopelagic respiration near the ESTOC (European Station for Time-Series in the Ocean, Canary Islands) site, located in the Eastern boundary region of the North Atlantic subtropical gyre. The tracer conservation model included vertical Ekman advection, geostrophic horizontal transport and vertical diffusion, and the biological remineralization terms were diagnosed by assuming steady state. Three different approaches were used to compute reference velocities used for the calculation of geostrophic velocities and flux divergences: a no-motion level at 3000 m, surface geostrophic velocities computed from the averaged absolute dynamic topography field, and surface velocities optimized from the temperature model. Mesopelagic respiration rates computed from the model were 2.8–8.9 mol O2 m2 y−1, 2.0–3.1 mol C m2 y−1 and 0.6–1.0 mol N m2 y−1, consistent with remineralization processes occurring close to Redfield stoichiometry. Model estimates were in close agreement with respiratory activity, derived from electron transport system (ETS) measurements collected in the same region at the end of the winter bloom period (3.61±0.48 mol O2 m−2 y−1). According to ETS estimates, 50% of the respiration in the upper 1000 m took place below 150 m. Model results showed that oxygen, DIC and nitrate budgets were dominated by lateral advection, pointing to horizontal transport as the main source of organic carbon fuelling the heterotrophic respiration activity in this region.